YSZ-based mixed potential type SO2 sensor adopting CexVyOz sensitive electrode material as well as preparation method and application of YSZ-based mixed potential type SO2 sensor

By using CexVyOz sensitive electrode material and high-pressure gas erosion technology in YSZ-based hybrid potential type SO2 sensors, the problem of difficulty in detecting existing sensors under harsh conditions is solved, and the rapid and sensitive detection of SO2 gas at high temperatures is achieved to meet the needs of industrial sites.

CN119688800APending Publication Date: 2025-03-25JIANGSU JINGCI INTELLIGENT SENSING TECH RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411648030.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing SO2 gas sensors are difficult to achieve stable and reliable high-concentration SO2 detection under harsh conditions such as high temperature, high humidity, and high aerial speed. The response speed is slow, the recovery time is long and the detection range is limited, making it difficult to meet the complex needs of industrial sites.

Method used

The YSZ-based hybrid potential SO2 sensor using CexVyOz sensitive electrode material improves the response speed and detection range of the sensor by optimizing the electrochemical catalytic activity of the sensitive electrode material, combining YSZ solid electrolyte and high-pressure gas erosion technology.

Benefits of technology

It realizes rapid response and high sensitivity detection to SO2 gas under high temperature conditions, has a wide detection range, good stability and durability, and meets the harsh conditions of industrial sites.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119688800A_ABST
    Figure CN119688800A_ABST
Patent Text Reader

Abstract

The invention relates to the field of gas sensors, in particular to a YSZ (Yttria Stabilized Zirconia)-based mixed potential type SO2 sensor adopting a CexVyOz sensitive electrode material as well as a preparation method and application of the YSZ-based mixed potential type SO2 sensor. The YSZ-based mixed potential type SO2 sensor adopting the CexVyOz sensitive electrode material comprises an Al2O3 substrate, a Pt heating electrode, a first YSZ electrolyte layer, a reference electrode, a second YSZ electrolyte layer and a sensitive electrode which are arranged in sequence, wherein the sensitive electrode comprises CexVyOz, CexVyOz and CexVyOz, according to the invention, YSZ is used as a solid electrolyte and an ion conducting layer, CexVyOz is used as a sensitive electrode material, SO2 gas can be monitored at a high temperature, the response speed is high at a high temperature and a high space speed, SO2 gas with a wide concentration can be tested, the testable temperature range is wide, strict condition testing can be met, and in-situ monitoring of the sensor is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of gas sensors, and in particular to a method using Ce x V y O z YSZ-based hybrid potential-type SO2 sensor of sensitive electrode material and its preparation method and application. Background Art

[0003] Accurate monitoring and effective control of SO2 emissions are of great significance to improving air quality, protecting the ecological environment and ensuring public health.

[0004] Although there are many SO2 gas sensors on the market, most of them are mainly for low-concentration detection (such as ppm or ppb level), which is difficult to meet the real-time, stable and reliable detection requirements of high-concentration SO2 (up to several hundred ppm) in industrial emission monitoring. At the same time, traditional sensors often have problems such as slow response speed, long recovery time, and limited detection range, which are difficult to meet the requirements of complex and changeable industrial field environments. In particular, under harsh conditions such as high temperature, high humidity, and high air speed, the stability and durability of the sensor are facing severe tests.

[0005] In this context, it is particularly urgent to explore and develop new high-performance SO2 gas sensors. Solid electrolyte sensors, especially hybrid potential sensors based on yttrium-stabilized zirconia (YSZ), have become a research hotspot due to their advantages such as low manufacturing cost, compact structure, good chemical stability, high sensitivity and excellent response recovery characteristics. This type of sensor uses the three-phase interface (TPB) between the sensitive electrode / SO2 gas / YSZ solid electrolyte to produce an electrochemical response. By optimizing the electrochemical catalytic activity of the sensitive electrode material, the detection performance of SO2 gas can be significantly improved. In addition, the sensitive electrode material to be developed is required to have specific adsorption of SO2 gas and good electrocatalytic activity.

[0006] Therefore, developing sensitive electrode materials with high electrochemical catalytic activity for SO2 and applying them to YSZ-based hybrid potential-type SO2 gas sensors has become a key approach to solving current monitoring problems. Summary of the invention

[0007] The purpose of the present invention is to provide a Ce-based tester that can meet the high temperature test environment, has good sensitivity, response / recovery characteristics, repeatability, stability and a wide detection range. x V y O z YSZ-based hybrid potential-type SO2 sensor of sensitive electrode material and its preparation method and application.

[0008] To achieve the above object, the technical solution adopted by the present invention is:

[0009] The first aspect of the present invention is to provide a method using Ce x V y O z The YSZ-based hybrid potential type SO2 sensor of sensitive electrode material comprises: an Al2O3 substrate, a Pt heating electrode, a first YSZ electrolyte layer, a reference electrode, a second YSZ electrolyte layer and a sensitive electrode arranged in sequence;

[0010] Wherein, the sensitive electrode comprises: Ce x V y O z .

[0011] Preferably, Ce x V y O z In, x:y:z=1:1:4.

[0012] The second aspect of the present invention is to provide a method for preparing the above-mentioned YSZ-based hybrid potential-type SO2 sensor, the steps comprising:

[0013] S1, tape casting to prepare an Al2O3 substrate, a first YSZ electrolyte layer and a second YSZ electrolyte layer;

[0014] S2, using screen printing technology to brush a Pt resistance circuit on the Al2O3 substrate and connect the Pt resistance circuit to the heating circuit, brush a reference electrode and a Pt wire connected to the reference electrode on the first YSZ electrolyte layer; brush another Pt wire and a Pt pin for connecting the sensitive electrode on the second YSZ electrolyte layer, and both Pt wires are connected to the Pt pin;

[0015] S3, stacking and fixing the Al2O3 substrate with a Pt heating electrode, the first YSZ electrolyte layer with a reference electrode, and the second YSZ electrolyte layer with a Pt pin in sequence, flushing the side of the first YSZ electrolyte layer close to the reference electrode with high-pressure gas to obtain a plurality of hollow gas flow channels, and then performing hot pressing and sintering treatment to obtain a SO2 sensor without brushing the sensitive electrode;

[0016] S4. Brush the sensitive electrode slurry onto the second YSZ electrolyte layer, connect another Pt wire to the sensitive electrode, and then perform sintering to obtain a YSZ-based hybrid potential-type SO2 sensor.

[0017] Preferably, in step S4, the preparation of the sensitive electrode slurry comprises: weighing a binder, Ce x V y O z The powder and fish oil were ground in a mortar.

[0018] More preferably, Ce x V y O z The preparation method of the powder includes: a sol-gel method, a solid phase method or a hydrothermal method.

[0019] More preferably, the sol-gel method is used to prepare Ce x V y O z The steps of preparing the powder include: weighing cerium nitrate and ammonium metavanadate according to the element ratio and dissolving them in deionized water; adding citric acid, EDTA and ammonia water after constant temperature stirring; adjusting the pH to 7-8.5; continuing stirring to obtain a gel; and drying and calcining the gel in turn to obtain Ce. x V y O z powder.

[0020] More preferably, the temperature of the constant temperature stirring is 70-75°C; the temperature of the drying treatment is 200-260°C, and the time is 4-12 hours; the temperature of the calcination treatment is 450-550°C, and the time is 2-3 hours.

[0021] More preferably, the amount of citric acid added is 1-4 times the amount of the metal ion, and the amount of EDTA added is 1-3 times the amount of the metal ion.

[0022] Preferably, in step S4, the sintering treatment comprises: heating to 800-1100°C at a rate of 1-4°C / min, sintering for 2h, and then cooling at a rate of 3-6°C / min.

[0023] The third aspect of the present invention is to provide an application of the above-mentioned YSZ-based hybrid potential type SO2 sensor or the YSZ-based hybrid potential type SO2 sensor prepared by the above-mentioned preparation method in detecting industrial exhaust gas SO2, wherein the temperature test range of the YSZ-based hybrid potential type SO2 sensor is 400-600°C, the SO2 test concentration is 0-500ppm, and the oxygen test range is 2-21%.

[0024] The present invention adopts the above technical solution, and has the following technical effects compared with the prior art:

[0025] (1) The sensitive electrode material Ce of the present invention x V y O zIt has high catalytic activity for SO2 gas; Ce ions, as a specific catalyst for SO2, have the advantage of rapid release / storage of lattice oxygen, which can greatly increase the rate of redox reaction. In addition, V2O5 has specific adsorption and catalysis for SO2. V, as a multivalent element, can increase the electrochemical catalytic activity of SO2 by changing its valence. The present invention utilizes the specific adsorption and catalytic activity of Ce and V elements for SO2 sensors to develop a new sensitive electrode material Ce. x V y O z The special morphology (diamond structure) of the sensitive electrode at 1000°C provides more catalytic sites for the material, which is beneficial to improving the electrocatalytic activity of SO2 gas, thereby improving the response of the sensor to SO2 gas.

[0026] (2) The present invention uses YSZ as the solid electrolyte and ion conductive layer, and Ce x V y O z As a sensitive electrode material, it can monitor SO2 gas at high temperature, has a fast response speed at high temperature and high air velocity, can test a wide concentration of SO2 gas, has a wide test temperature range, can meet the test of harsh conditions, and is conducive to the in-situ monitoring of the sensor;

[0027] (3) The sensitive electrode of the present invention is firmly bonded to the YSZ electrolyte layer and is not easy to fall off, which is conducive to the use of the sensor at high air speed.

[0028] (4) The sensor of the present invention flushes out channels on the YSZ electrolyte layer between the reference electrode and the Pt heating electrode through high-pressure gas, providing a channel for the reference electrode to contact the external environment, ensuring the stability of the initial voltage and reducing the impact on the SO2 gas mixing potential test results. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 A schematic diagram of the basic structure of a YSZ-based hybrid potential type SO2 sensor in one embodiment of the present invention;

[0030] Figure 2 XRD patterns of CeVO4 calcined at 500℃ and sensitive electrodes at different sintering temperatures;

[0031] Figure 3 Schematic diagram of the microscopic morphology of CeVO4 calcined at 500℃;

[0032] Figure 4 Schematic diagram of the microscopic morphology of the sensitive electrode at different sintering temperatures of 800-1100℃;

[0033] Figure 5The response size comparison of the sensor constructed with CeVO4 sensitive electrode at 0-500ppm and the sensitivity curve to SO2 gas at a sintering temperature of 800-1100℃; where a is the response size comparison of the sensor at 0-500ppm, and b is the sensitivity curve of the sensor to SO2;

[0034] Figure 6 The following is a comparison of the response size of the sensor constructed with CeVO4 sensitive electrode at 0-500ppm and the sensitivity curve to SO2 gas at an operating temperature of 400-600℃; where a is the comparison of the response size of the sensor at 0-500ppm, and b is the sensitivity curve of the sensor to SO2;

[0035] Figure 7 Comparison of the response recovery time of the sensor constructed with CeVO4 sensitive electrode to 100ppm SO2 and 500ppm SO2 at an operating temperature of 400-600℃;

[0036] Figure 8 The stability of the sensor constructed with CeVO4 sensitive electrode at 600℃ working temperature;

[0037] Fig. 9 The response of the sensor built with CeVO4 sensitive electrode to 100ppm SO2 at different oxygen concentrations at an operating temperature of 600℃. DETAILED DESCRIPTION

[0038] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.

[0040] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments, but they are not intended to limit the present invention.

[0041] Example

[0042] like Figure 1 As shown, this embodiment provides a YSZ-based hybrid potential-type SO2 sensor using CeVO4 sensitive electrode material and a preparation method thereof, the steps comprising:

[0043] S1, tape casting to prepare an Al2O3 substrate, a first YSZ electrolyte layer and a second YSZ electrolyte layer;

[0044] S2, using screen printing technology to brush a Pt resistance circuit on the Al2O3 substrate and connect the Pt resistance circuit to the heating circuit, brush a reference electrode and a Pt wire connected to the reference electrode on the first YSZ electrolyte layer; brush another Pt wire and a Pt pin for connecting the sensitive electrode on the second YSZ electrolyte layer, and both Pt wires are connected to the Pt pin;

[0045] S3, stacking and fixing the Al2O3 substrate with a Pt heating electrode, the first YSZ electrolyte layer with a reference electrode, and the second YSZ electrolyte layer with a Pt pin in sequence, flushing the side of the first YSZ electrolyte layer close to the reference electrode with high-pressure gas to obtain a plurality of hollow gas flow channels, and then performing hot pressing and sintering treatment to obtain a SO2 sensor without brushing the sensitive electrode;

[0046] S4, brush the sensitive electrode slurry onto the second YSZ electrolyte layer, connect another Pt wire to the sensitive electrode, and then perform sintering treatment, the sintering temperature is 1000℃, the sintering time is 2h, the heating rate is 2℃ / min, and the cooling rate is 5℃ / min, so as to obtain a YSZ-based hybrid potential type SO2 sensor;

[0047] The preparation of the sensitive electrode slurry includes: weighing 0.8g of a binder, 1.2g of CeVO4 powder and 0.02g of fish oil and grinding them in a mortar until the slurry has good thixotropy and fluidity;

[0048] The steps of preparing CeVO4 powder include: weighing 1mmol cerium nitrate and 1mmol ammonium metavanadate according to the element ratio of Ce:V=1:1 and dissolving them in deionized water, adding 3mmol citric acid and 2mmol EDTA after constant temperature stirring at 75°C, adding ammonia water to adjust the pH to 7, and continuing to stir to obtain gel, drying the gel at 240°C for 4h to obtain dry gel, and then calcining the dry gel at 500°C for 2h to obtain CeVO4 powder.

[0049] Detection Example

[0050] The morphology of CeVO4 powder and sensitive electrode was tested. The results are as follows: Figure 2-4 As shown;

[0051] After calcination at 500℃ for 2h, pure phase CeVO4 powder with tetragonal crystal structure was obtained, which corresponds well to the standard card JCPDS#82-1969, and no other impurities appear; the sharp XRD peak shows that the synthesized CeVO4 nanoparticles have excellent crystallinity; after the sensor is sintered at different temperatures (800-1100℃), the obtained XRD spectrum matches well with the standard cards JCPDS#82-1969 (CeVO4) and JCPDS#82-1246 (YSZ), and the diffraction peak is narrow, sharp and strong, indicating that its crystallinity is high ( Figure 2 );

[0052] The particle size of the powder calcined at 500℃ for 2h is about 20-70nm, and the powder is connected into large blocks ( Figure 3 ); With the increase of sintering temperature, the sensitive electrode particles grow and the pores become larger; after sintering at 1000℃, the particles approach a rhombus structure and more specific crystal faces appear, which is beneficial to the improvement of the catalytic performance of the sensitive electrode material ( Figure 4 ).

[0053] The YSZ-based hybrid potential SO2 sensor described in the embodiment is firmly inserted into a cylindrical ceramic block, which is then placed in a metal shell. An appropriate amount of talcum powder is then filled into the metal shell as a sealing material, and pressure is applied through a piezoelectric feeder mold to ensure that the talcum powder is tightly compacted in the shell to form an effective seal. The positive side wiring port of the sensor is connected to an electrochemical workstation, and a dynamic test is used to test the voltage change of the sensor in a 0-500ppm SO2 atmosphere at an air flow rate of 4000mL / min and an O2 concentration of 21%. The results are as follows: Figure 5-9 As shown;

[0054] At the same working temperature, the response value of the sensor first increases and then decreases with the increase of sintering temperature. The sensor sintered at 1000℃ has the largest response to SO2 gas. In 500ppm SO2 gas, the response potential difference reaches -69.73mV ( Figure 5 a). The sensitivity curve of the SO2 sensor at different sintering temperatures shows that the sensor's response to SO2 gas is negatively linear at different sintering temperatures, which is consistent with the mixed potential principle. The sensitivity reaches its maximum at 1000°C, with a value of -25.92mv / decade ( Figure 5 b);

[0055] At the same operating temperature, the response value of the sensor increases inversely with the increase of SO2 concentration; at 600℃ operating temperature and 500ppm SO2 gas, the response potential difference reaches -15.84mv ( Figure 6 );

[0056] At 600℃, the response recovery characteristics are the best. The response and recovery time of the sensor to 100ppm SO2 gas are 31s and 41s respectively; the response and recovery time to 500ppm SO2 gas are 11s and 33s respectively. Figure 7 );

[0057] At 600℃ working temperature, the sensor has good repeatability and stability in low concentration 100ppm SO2 and high concentration 500ppm SO2 gas ( Figure 8 ), which is conducive to promoting the application of sensors in the field of industrial exhaust gas.

[0058] The sensor response is positively linear with the logarithm of oxygen concentration ( Fig. 9 ), which conforms to the principle of mixed potential. Under normal circumstances, the oxygen content of industrial exhaust gas is around 3%-21%, which is conducive to the application of sensors in industrial exhaust gas detection.

[0059] In summary, this patent is based on the YSZ-based hybrid potential sensor chip. x V y O z Composite oxides are used as sensitive electrodes to construct a new hybrid potential SO2 sensor, which can test SO2 gas under dynamic conditions of high temperature and high space velocity, and is conducive to promoting the commercialization of the sensor in the field of industrial exhaust SO2 gas detection. The sensor prepared by the present invention has high response and sensitivity to SO2 gas at high temperature, good response / recovery characteristics and repeatability, and a wide response range.

[0060] The above description is only a preferred embodiment of the present invention, and does not limit the implementation mode and protection scope of the present invention. For those skilled in the art, it should be aware that all solutions obtained by equivalent substitutions and obvious changes made using the description and illustrations of the present invention should be included in the protection scope of the present invention.

Claims

1. A method using Ce x V y O z The YSZ-based hybrid potential-type SO2 sensor with sensitive electrode material is characterized by: include: An Al2O3 substrate, a Pt heating electrode, a first YSZ electrolyte layer, a reference electrode, a second YSZ electrolyte layer and a sensitive electrode are sequentially arranged; Wherein, the sensitive electrode comprises: Ce x V y O z .

2. The YSZ-based hybrid potential type SO2 sensor according to claim 1, characterized in that: Ce x V y O z where x:y:z = 1:1:

4.

3. A method for preparing a YSZ-based hybrid potential-type SO2 sensor as claimed in any one of claims 1 to 2, characterized in that the steps include: S1, tape casting to prepare an Al2O3 substrate, a first YSZ electrolyte layer and a second YSZ electrolyte layer; S2, using screen printing technology to brush a Pt resistance circuit on the Al2O3 substrate and connect the Pt resistance circuit to the heating circuit, brush a reference electrode and a Pt wire connected to the reference electrode on the first YSZ electrolyte layer; brush another Pt wire and a Pt pin for connecting the sensitive electrode on the second YSZ electrolyte layer, and both Pt wires are connected to the Pt pin; S3, stacking and fixing the Al2O3 substrate with a Pt heating electrode, the first YSZ electrolyte layer with a reference electrode, and the second YSZ electrolyte layer with a Pt pin in sequence, flushing the side of the first YSZ electrolyte layer close to the reference electrode with high-pressure gas to obtain a plurality of hollow gas flow channels, and then performing hot pressing and sintering treatment to obtain a SO2 sensor without brushing the sensitive electrode; S4. Brush the sensitive electrode slurry onto the second YSZ electrolyte layer, connect another Pt wire to the sensitive electrode, and then perform sintering to obtain a YSZ-based hybrid potential-type SO2 sensor.

4. The preparation method according to claim 3, characterized in that: In step S4, the preparation of the sensitive electrode slurry includes: weighing the binder, Ce x V y O z The powder and fish oil were ground in a mortar.

5. The preparation method according to claim 4, characterized in that: Ce x V y O z The preparation method of the powder includes: a sol-gel method, a solid phase method or a hydrothermal method.

6. The preparation method according to claim 5, characterized in that: Preparation of Ce by Sol-Gel Method x V y O z The steps of powder include: Weigh cerium nitrate and ammonium metavanadate according to the element ratio and dissolve them in deionized water. After constant temperature stirring, add citric acid, EDTA and ammonia water. After adjusting the pH to 7-8.5, continue stirring to obtain a gel. The gel is dried and calcined in turn to obtain Ce. x V y O z powder.

7. The preparation method according to claim 6, characterized in that: The temperature of the constant temperature stirring is 70-75°C; the temperature of the drying treatment is 200-260°C, and the time is 4-12h; the temperature of the calcination treatment is 450-550°C, and the time is 2-3h.

8. The preparation method according to claim 6, characterized in that: The amount of citric acid added is 1-4 times the amount of metal ions, and the amount of EDTA added is 1-3 times the amount of metal ions.

9. The preparation method according to claim 3, characterized in that: In step S4, the sintering treatment includes: heating to 800-1100°C at a rate of 1-4°C / min, sintering for 2h, and then cooling at a rate of 3-6°C / min.

10. An application of the YSZ-based hybrid potential-type SO2 sensor as claimed in any one of claims 1 to 2 or the YSZ-based hybrid potential-type SO2 sensor prepared by the preparation method as claimed in any one of claims 3 to 9 in detecting industrial tail gas SO2, characterized in that: The temperature test range of the YSZ-based hybrid potential SO2 sensor is 400-600°C, the SO2 test concentration is 0-500ppm, and the oxygen test range is 2-21%.